Biomedical Ethics and Human Rights in The Context of Innovation and Information Development of Society - Kalyuzhny, Rostislav; Makeieva, Olena; Shapenko, Lyudmila (Journal of History Culture and Art Research, 2020)
The article is devoted to the issues of biomedical ethics and human rights in the conditions of innovation and information development of society. The factors of the emergence of modern biomedical ethics under the evolution of biology and medicine, including innovative technologies. Under "biomedical ethics," the branch of knowledge is considered, which is a system of ethical and legal norms that regulate relations in the field of biomedicine, a set of moral principles, norms and rules that medical professionals should observe in the course of professional activity. Sources of biomedical ethics are singled out: national legislation in the field of medicine; international medical law regulating legislation; international ethical (deontological) codes containing recommendations on medical ethics; national ethical (deontological) codes of professional ethics of medical staff. The basic functions of biomedical ethics are disclosed: informational, axiological (value), communicative, preventive. The issue of ratification by the Verkhovna Rada of Ukraine of international acts as a condition for ensuring the protection of human rights is explored. The expediency of adopting a special law "On the Protection of Patients’ Rights", which determines the legal, economic and organizational foundations for the protection of the rights and legitimate interests of patients, including biomedical ones, is substantiated. The need to overcome the gaps in the legislation of Ukraine by unifying and developing concepts in the field of biomedicine, the normative consolidation of ethical requirements for medical staff and the implementation of biomedical research and medical practice, as well as the responsibilities of patients, is emphasized. The emphasis placed on the need to improve the domestic health care model through the introduction of a public-private partnership in healthcare. The importance of creating a system of organizational and legal measures to improve control over the implementation of laws and regulations on the observance of the legality of processing personal data through the establishment of rules of legal responsibility, the provision of the use of electronic services in order to implement the rights of patients, the development of criteria-signs of the concept of "personal data". The prospect of further research on biomedical ethics and human rights through the improvement of legal theory and legal practice is determined. It is concluded that fundamental human rights should remain the basis for solving existing ethical and legal problems in the field of biomedicine.